2000
DOI: 10.1080/096708700415526
|View full text |Cite
|
Sign up to set email alerts
|

Development of leaf rust (Peridiopsora mori) and dispersal of urediniospores in mulberry (Morusspp.)

Abstract: Studies were conducted on the effect of pruning time, host age, urediniospore release and weather parameters on the incidence and intensity of mulberry leaf rust (Peridiopsora mori). Rust severity significantly increased with increasing shoot age, irrespective of pruning time. Maximum disease severity was observed in plants pruned during the third week of October, and minimum severity in plants pruned during last week of November. Apparent infection rate was higher in younger shoots. Infection rate was higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…As leaves age, longer period of leaf wetness is required for infection (Turechek and Stevenson, 1998). Similar results on the higher disease severity in older plants were reported in case of rust infection in mulberry (Pratheesh Kumar et al, 2000). The susceptible stage in a plant may appear after the pathogen inoculum has been weakened or exhausted.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…As leaves age, longer period of leaf wetness is required for infection (Turechek and Stevenson, 1998). Similar results on the higher disease severity in older plants were reported in case of rust infection in mulberry (Pratheesh Kumar et al, 2000). The susceptible stage in a plant may appear after the pathogen inoculum has been weakened or exhausted.…”
Section: Discussionsupporting
confidence: 69%
“…The higher apparent infection rate per unit area per day in young plants rather than in the mature old ones observed may be due to the establishment and colonization of the pathogen in the early growing stage and thereafter the growth of pathogen in a steady rate. The fungi utilize food material available in the leaves for the establishment and colonization which causes a deficit in food materials for subsequent growth of the pathogen reducing in the apparent rate of infection in more mature and older plants (Pratheesh Kumar et al, 2000). Environment influence the epidemics of diseases through its various structural elements.…”
Section: Discussionmentioning
confidence: 99%
“…Pratheesh Kumar et al (2000) reported that leaf rust disease severity shows significant correlation with temperature and rainfall in plains of West Bengal. Maji et al (2010) reported that leaf rust has significant negative correlation with maximum and minimum RH, number of rainy days and positive correlation with bright sunshine hours.…”
Section: Resultsmentioning
confidence: 99%
“…Weather based disease prediction models have been developed for management of wheat rust (Eversmeyer et al 1973;Nagarajan and Singh 1975;. In mulberry, Pratheesh Kumar et al (2000) developed forecasting equation of leaf rust of the Gangetic plains of West Bengal. Maji et al (2010) developed forecasting models of leaf rust for Orissa region.…”
Section: Introductionmentioning
confidence: 99%